A Review of Progress on Targeting LDL Receptor-Dependent and -Independent Pathways for the Treatment of Hypercholesterolemia, a Major Risk Factor of ASCVD - Rai Ajit K. Srivastava (Cells, 2023)
Since the discovery of the LDL receptor in 1973 by Brown and Goldstein as a causative protein in hypercholesterolemia, tremendous amounts of effort have gone into finding ways to manage high LDL cholesterol in familial hypercholesterolemic (HoFH and HeFH) individuals with loss-of-function mutations in the LDL receptor (LDLR) gene. Statins proved to be the first blockbuster drug, helping both HoFH and HeFH individuals by inhibiting the cholesterol synthesis pathway rate-limiting enzyme HMG-CoA reductase and inducing the LDL receptor. However, statins could not achieve the therapeutic goal of LDL. Other therapies targeting LDLR include PCSK9, which lowers LDLR by promoting LDLR degradation. Inducible degrader of LDLR (IDOL) also controls the LDLR protein, but an IDOL-based therapy is yet to be developed. Among the LDLR-independent pathways, such as angiopoietin-like 3 (ANGPTL3), apolipoprotein (apo) B, apoC-III and CETP, only ANGPTL3 offers the advantage of treating both HoFH and HeFH patients and showing relatively better preclinical and clinical efficacy in animal models and hypercholesterolemic individuals, respectively. While loss-of-LDLR-function mutations have been known for decades, gain-of-LDLR-function mutations have recently been identified in some individuals. The new information on gain of LDLR function, together with CRISPR-Cas9 genome/base editing technology to target LDLR and ANGPTL3, offers promise to HoFH and HeFH individuals who are at a higher risk of developing atherosclerotic cardiovascular disease (ASCVD).